2022
DOI: 10.5194/acp-22-1-2022
|View full text |Cite
|
Sign up to set email alerts
|

Modeled and observed properties related to the direct aerosol radiative effect of biomass burning aerosol over the southeastern Atlantic

Abstract: Abstract. Biomass burning smoke is advected over the southeastern Atlantic Ocean between July and October of each year. This smoke plume overlies and mixes into a region of persistent low marine clouds. Model calculations of climate forcing by this plume vary significantly in both magnitude and sign. NASA EVS-2 (Earth Venture Suborbital-2) ORACLES (ObseRvations of Aerosols above CLouds and their intEractionS) had deployments for field campaigns off the west coast of Africa in 3 consecutive years (September 201… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 161 publications
2
21
0
Order By: Relevance
“…The 2017 and 2018 IOPs had 10 PRFs with overlapping flight tracks when the aircraft flew south from 0 • N, 5 • E toward 15 • S, 5 • E and returned along the same track. PRFs with overlapping tracks acquired statistics for model evaluation (Doherty et al, 2022), while the other PRFs targeted specific locations based on meteorological conditions .…”
Section: Observationsmentioning
confidence: 99%
“…The 2017 and 2018 IOPs had 10 PRFs with overlapping flight tracks when the aircraft flew south from 0 • N, 5 • E toward 15 • S, 5 • E and returned along the same track. PRFs with overlapping tracks acquired statistics for model evaluation (Doherty et al, 2022), while the other PRFs targeted specific locations based on meteorological conditions .…”
Section: Observationsmentioning
confidence: 99%
“…Southern Africa region produces approximately one-third of the world's fire-emitted carbon (van der Werf et al, 2010). The global maximum of absorbing aerosol above cloud occurs above the southeast Atlantic (Waquet et al, 2013), a combination that produces a direct radiative warming of the regional climate (Keil and Haywood, 2003;Graaf et al, 2014;Zuidema et al, 2016;Mallet et al, 2021;Doherty et al, 2022). Biomass-burning aerosol (BBA) from this region is unusual for being highly absorbing of sunlight, with SSA values of 0.85 or less at the green wavelength (Zuidema et al, 2018;Chylek et al, 2019;Pistone et al, 2019;Holanda et al, 2020;Taylor et al, 2020;Denjean et al, 2020b;Mallet et al, 2020;Shinozuka et al, 2020;Carter et al, 2021;Brown et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These model biases introduce some uncertainties into our results, particularly with respect to the effects of BB aerosols on CCN and clouds. In addition, Doherty et al (2022) showed that cloud cover is biased high in this region, at least for the 2017 biomass burning season, which could also lead to an overestimation of CRE. As a result, our results are subject to a certain level of model uncertainties.…”
Section: Discussionmentioning
confidence: 95%